Evaluation of Protein Ubiquitylation in Heart Tissue of Rats Exposed to Diazinon (an Organophosphate Insecticide) and Crocin (an Active Saffron Ingredient): Role of HIF-1α - Razavi, B. M.; Hosseinzadeh, H.; Imenshahidi, M.; Malekian, M.; Ramezani, M.; Abnous, K. (Drug Research, 2015)
Introduction:  Organophosphate compounds, such as diazinon (DZN), are widely used in agriculture and can lead to formation of reactive oxygen species (ROS) in cardiovascular system. ROS are highly toxic since they can cause serious changes in proteins including ubiquitylation. Crocin (a carotenoid isolated from saffron), has protective effects against DZN cardiotoxicity. In this study level of total protein ubiquitylation as markers of oxidative stress and level of ubiquitin-HIF-1α and P53, known substrates of ubiquitylation, in rat hearts exposed to DZN and crocin were evaluated.Methods:  Rats were divided into 7 groups: corn oil (control), DZN (15 mg/kg/day, gavage), crocin (12.5, 25, 50 mg/kg/day, i. p.) plus DZN, vitamin E (200 IU/kg, i. p., 3 days a week) plus DZN and crocin (50 mg/kg/day, i. p.). Treatments were continued for 4 weeks. Total protein ubiquitylation, total HIF-1α and P53 were analyzed by western blotting. Total HIF-1α and P53 were purified by immunoprecipitation (IP) and ubiquitin- HIF-1α and P53 were analyzed by western blotting.Results:  Higher protein ubiquitylation levels were observed in DZN treated rats. Decrease in ubiquitin-HIF-1α was also shown, and leads to higher HIF-1α protein levels in DZN group. Crocin (50 mg/kg) and vit. E protected cells against DZN protein ubiquitylation. Significant differences were not observed between the ubiquitin – P53 and total P53 protein levels.Conclusion:  Our results showed that ubiquitylation could be considered as a marker of oxidative stress in rats exposed to DZN. Increase in level of HIF-α may compensate adverse effect of DNZ in rat heart.
Keywords: diazinon; ubiquitylation; HIF-1α; P53; immunoprecipitation